Demographic and Socio-Eeconomic Characteristics of Patients with Congestive Heart failure Presenting to the Cardiac Emergency of Bangabandhu Sheikh Mujib Medical University (University Heart Journal, 2018)
Background: Repeated hospital readmissions are frequent and increasing over time in patients with heart failure (HF). The readmission rate within 3-6 months after discharge in these patients is 10-50%.Aim and Objective: This study was conducted to find out the demographic and socioeconomic factors contributing to readmission of patients with congestive heart failure admitted in university cardiac center of Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka, Bangladesh during last quarter of 2016 and early quarter of 2017.Material and method: This was observational descriptive cross sectional study and enrolled 102 patients were enrolled for the study. Complete medical records were reviewed carefully.Results:A total of 68 men and 34 women with a mean (±SD) age of 55 (±14) years constitute the study population. Most of the population (42%) who belongs to age group 51-60 years had readmissions (p